"Cutis tricolor": congenital hyper- and hypopigmented macules associated with a sporadic multisystem birth defect: an unusual example of twin spotting?. Issue 8 (August 1997) - Happle, R; Barbi, G; Eckert, D; Kennerknecht, I
Abstract : An uncommon coexistence of circumscribed hyperpigmentation and hypopigmentation, in close proximity to each other, is described in a 17 years old patient with various other cogenital defects, such as dysmorphic facial appearance, severe kyphoscoliosis, delayed motor development, epileptic seizures, and mental retardation. We suggest the combination of hyper- and hypopigmented cutaneous lesions is an example of allelic twin spotting. Because the skin of this patient showed three different degrees of pigmentation the term "cutis tricolor" is proposed.